The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1981
DOI: 10.1083/jcb.91.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of minor components of coated vesicles by use of permeation chromatography.

Abstract: Coated vesicles are thought to be vehicles for the intracellular transport of membranes . Clathrin is the major protein component of coated vesicles . Minor components of these organelles can be identified in highly purified preparations if they can be shown to copurify with clathrin . To show copurification we have made use of the relatively uniform diameter of coated vesicles (50-150 nm) to fractionate conventionally purified coated vesicles according to size on glass bead columns of 200-nm pore size . We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Our finding that the types of transport vesicles that utilize clathrin are morphologically diverse structures is consistent with the current knowledge of such structures (Pfeffer and Kelly 1981). Consistent with what is known concerning clathrin-coated vesicles, we observed that the typical unit membrane vesicles, which range in size from 50Á150 nM, were coated with clathrin.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that the types of transport vesicles that utilize clathrin are morphologically diverse structures is consistent with the current knowledge of such structures (Pfeffer and Kelly 1981). Consistent with what is known concerning clathrin-coated vesicles, we observed that the typical unit membrane vesicles, which range in size from 50Á150 nM, were coated with clathrin.…”
Section: Discussionsupporting
confidence: 92%
“…The characterization of these carriers has played a major role in the functional dissection of coat-dependent sorting and vesiculation mechanisms. For example, vesicles "in a basket" isolated from brain led to the biochemical identification of the first sorting machinery, clathrin and the AP-1 and AP-2 adaptors (Kanaseki and Kadota, 1969;Pearse, 1975;Pfeffer and Kelly, 1981;Pearse and Crowther, 1987). Subsequent studies of cargo molecules in brain clathrin-coated vesicles were crucial in revealing mechanisms of synaptic vesicle recycling (Pfeffer and Kelly, 1985;Maycox et al, 1992;Blondeau et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since conventional preparations of coated vesicles contain both endocytic and Golgi-derived vesicles, the fact that these fractions have been found to contain ATP-dependent acidification activity does not establish the intracellular origin of the endosomal proton pump. Moreover, since coated vesicle acidification is typically monitored using nonselective externally added pH probes (e.g., acridine orange), interpretation may be further complicated by the presence of small amounts of V-ATPase-containing uncoated membranes in the coated vesicle fraction (7).…”
mentioning
confidence: 99%